2016
DOI: 10.1001/jamaneurol.2015.4321
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Clinical Effects of Mesenchymal Stem Cells Secreting Neurotrophic Factor Transplantation in Patients With Amyotrophic Lateral Sclerosis

Abstract: IMPORTANCE Preclinical studies have shown that neurotrophic growth factors (NTFs) extend the survival of motor neurons in amyotrophic lateral sclerosis (ALS) and that the combined delivery of these neurotrophic factors has a strong synergistic effect. We have developed a culture-based method for inducing mesenchymal stem cells (MSCs) to secrete neurotrophic factors. These MSC-NTF cells have been shown to be protective in several animal models of neurodegenerative diseases. OBJECTIVE To determine the safety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(190 citation statements)
references
References 37 publications
9
166
1
6
Order By: Relevance
“…[4][5][6][7] Although still debated, MSCs from adipose and bone marrow have similar properties, and adipose harvesting is a simpler, well-tolerated procedure. These safety data support the exploration of adipose-derived MSCs in other neurologic conditions.…”
Section: Results After Providing Institutional Reviewmentioning
confidence: 99%
“…[4][5][6][7] Although still debated, MSCs from adipose and bone marrow have similar properties, and adipose harvesting is a simpler, well-tolerated procedure. These safety data support the exploration of adipose-derived MSCs in other neurologic conditions.…”
Section: Results After Providing Institutional Reviewmentioning
confidence: 99%
“…One million cells/sites at 24-48 separate sites were injected to the biceps and triceps, and 1-2 × 10 after the administration of cells. The authors also reported an improvement in the decline of ALSFRS-R within 6 month of follow-up period compared to the run-in period, from −1.2 to 0.6 points/month, and also a decline from −5.1% to −1.2%/month in the predicted forced vital capacity [168]. The safety and efficacy of MSC-NTF cells were further tested in a randomized, double-blinded phase IIb clinical trial in 48 ALS patients, divided in a ratio of 3:1 between treatment and placebo arms, respectively (NCT02017912).…”
Section: Clinical Trials Using Cell-based Therapies For the Treatmentmentioning
confidence: 81%
“…Moreover, intravenously infused MSCs have been shown to improve the outcomes of acute renal, neural and lung injury, perhaps leading to a switch from proinflammatory to anti-inflammatory cytokines at the site of injury [49]. Many studies have focused on the potential use of BMSCs for the treatment of degenerative diseases, stroke, myocardial infarction and autoimmune diseases [50][51][52][53][54].…”
Section: Unique Properties Of Bmscsmentioning
confidence: 99%